2021
DOI: 10.21744/lingcure.v5ns2.1357
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and pedagogical aspects of consolidation of social capital of higher education institutions

Abstract: The aim of the study was to identify psychological and pedagogical factors that ensure the consolidation of social capital in higher education institutions and to assess their effectiveness through expert critical evaluations. The study used the exploratory design and was based on the use of qualitative methods to evaluate the selected studies. The research methodology relied on the methods recommended for feasibility studies to determine the possibility of implementation of the selected best practices. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The lower the frequency of contact, the higher the level of depression and anxiety in adulthood, the lower the level of self-esteem, the more interpersonal troubles, and the less positive coping styles are used. Compared with non-poor university students, poor university students have lower social support ( Bocheliuk et al, 2021 ). Zhang and University (2017) found that the health status of non-poor children was better than that of poor children and poor children.…”
Section: Related Workmentioning
confidence: 99%
“…The lower the frequency of contact, the higher the level of depression and anxiety in adulthood, the lower the level of self-esteem, the more interpersonal troubles, and the less positive coping styles are used. Compared with non-poor university students, poor university students have lower social support ( Bocheliuk et al, 2021 ). Zhang and University (2017) found that the health status of non-poor children was better than that of poor children and poor children.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies of the Russian educational tradition have been published in the last few decades, reflecting the critical elements of a creative learning environment without interruption which, in a sense, is what this is exploring as its main focus. Essays documenting creative teaching and learning have become an essential part of the study of inherited concepts since they have helped to determine the direction towards which special education and education, in general, will be improved [4,6].…”
Section: Clear the Goal Of Art Teachingmentioning
confidence: 99%